Local multipliers in United States cities: a replication of Moretti (2010) - van Dijk, J (University of Oxford, 2015)
This paper replicates Moretti (AER, 2010). I estimate the local employment multiplier between the tradable and the nontradable sector in MSAs in the United States using two methods. The first replicates Moretti's results, based on the description he gives in his paper and part of his estimation files. I am able to reverse engineer the specification he uses, but identify some discrepancies with his results. The second method is an alternative to his specification that produces more robust estimates of the local multiplier effect with more policy relevance. Using an alternative instrument which, I argue is more plausibly exogenous, I find that for each 100 new jobs in the tradable sector, there are 84 additional jobs created in the nontradable sector of the same city. This is 75 fewer jobs than predicted by Moretti.